PEMIKIRAN HUKUM ISLAM; (Studi Pembaruan Hukum Islam Asy-Syatibi & Ibnu Taimiyah) - Syihab, Mahdi Abdullah (State of Islamic Institute Langsa, 2017)
This article would like to explain about Fiqh thought of Asy Syatibi and Ibnu Taimiyah around Islamic Law. These two figures  are  known  as  innovators  in  Islamic  Law.  Asy Syatibi is popular in Granada and his thought in Islamic law  certainly  influenced  by  social  culture  in  Granada.  He applies  the  principle  of  ?Mura?at  al-Khilaf?,  which  is  a principle to honor dissenting opinion in a way that  look at all the opinion as correct. Contrary to Ibnu Taimiyyah, his thought  in  Islamic  law  influenced  by  social  culture  in Damascus.  As  a  result,  the  basic  principle  of  Ibnu Taimiyyah?s fatwa more resemble to Ahmad ibn Hambal?s thought  in  the  use  of  existing  legal    sources.  Neverthless, Ibnu  Taimiyyah  keep  looking  ?illat?  (legal  reasoning)  and base his opinion to that ??illats?.